Practical Remote Workflow Solutions for Complex Digital Projects: Opportunities in a Pandemic. Issue 2 (June 2022) - Pryse, J.A.
The spread of COVID-19 has created numerous challenges in the field of archive management. Limited in-house office space, furloughs of personnel, and inconsistency, has highlighted the potential for the Carl Albert Congressional Research and Studies Center Archives (Center) to develop and implement improved accessibility measures to thousands of linear feet of material. Addition ally, the Center has found unique opportunities to collaborate with multiple academic institutions to propose large-scale digitization program exhibitions using the Center's remote workflow model. One of the largest, most complex collections the Center has worked with during this time is the Political Commercial Collection (the Collection), which holds 119, 000 film, audio, and videotape recordings of commercials aired between 1936 and present. It is the largest collection of political commercials in the world. The Center has developed a working pilot digitization project that has currently resulted in access to 16, 000 digital videos for public researchers and over 10, 000 available for on-line streaming during the pilot phase between April 16, 2020, and December 1, 2020. This paper presents the practical application of the Center's simplified "Linear Reciprocity Workflow Model" to provide a systematic solution for digital and long-term preservation of complex collections. The Center has proven that limited personnel and reduced resources need not interrupt continued access to archival repositories.